The complete mitochondrial genome of Fopius arisanus (Sonan 1932) (Hymenoptera: Braconidae). Issue 1 (2nd January 2022) - Cai, Pumo; Yang, Deqing; Hao, Xuxing; Yue, Guoqing; Jiang, Lili; Xiao, Kang; Jia, Pingfan; Yang, Jianquan; Ji, Qing'e; Lin, Jia
Abstract: Fopius arisanus (Sonan, 1932), an important egg parasitoid of several notorious tephritid pests, plays a key role in biological control programs. In the present study, the whole mitochondrial genome of F . arisanus was sequenced and characterized. The mitogenome of F . arisanus is 16, 425 bp in length with 14.94% GC content, and contains 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and two ribosomal RNA genes (rRNAs). The phylogenetic trees demonstrated that F . arisanus is sister group to Psyttalia concolor, P. humilis, P. lounsburyi and Diachasmimorpha longicaudata.